PRESERVING THE TRADITION OF KASAB CRAFT IN NAGAN RAYA DISTRICT - Sri Ayuda; Husaini Husda; Asmanidar (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
Kasab or kasab cloth, is a traditional textile embroidered with various types of local motifs in Keude Blang Village, Seunagan Timur District, Nagan Raya Regency, Aceh. However, the cultural richness of this society has never been scientifically researched. Therefore, the purpose of this study was to find out the types of motifs and the preservation of objects by the community and local government in that area. This is qualitative research, data collection involved observation, interviewing, and documentation. The results showed that kasab is one of the traditions for embroidering motifs on traditional textile surfaces. The use of gold thread in the components of traditional ceremonies not only provides aesthetic value, but also complements the meaning conveyed through symbols as a medium of public communication. The kasab motifs that are always embroidered in the Keude Blang Ara Village community include the bungong uret, bungong meulu, bungong pucuk pakis, and pucuk rembong (bamboo flower) motifs. Kasab preservation in Keude Blang Ara Village continues to be carried out by the local community and supported by the government. Preserving local culture (kasab) involves creating dynamic expressions and adapting to changing developmental situations to preserve cultural, artistic, and traditional qualities. However, with the support of the government, kasab has become something interesting, so that nowadays the demand for producing kasab is increasing.